2016
DOI: 10.1016/j.jallcom.2015.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of γ-Fe precipitate in Cu-2%Fe alloy aged under high magnetic field

Abstract: Cu-2wt%Fe alloy, an inexpensive candidate for a high strength conductor, depends for its conductivity on the precipitation of Fe. We applied an external 12 T high magnetic field (HMF) during ageing treatment of this alloy in order to study the resulting γ-Fe precipitation on the electrical conductivity. When the alloy was aged at 450 °C for up to 16 hrs, coherent γ-Fe precipitates formed within the Cu matrix. Between the γ-Fe precipitates and the Cu matrix, the lattice misfit was 1.4%±0.7% and the angle betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 46 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…Fe precipitates with diameters of ~5 nm were observed after ageing at 550 °C in Fe-doping alloy ( Figure 6 a). Our previous result indicated that Fe precipitates and the Cu matrix had a cube-on-cube orientation relationship [ 21 ]. Magnetization curves of both the Fe-free alloy and the Fe-doping alloy after a heat treatment, aged at 550 °C for 4 h, are shown in Figure 6 b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe precipitates with diameters of ~5 nm were observed after ageing at 550 °C in Fe-doping alloy ( Figure 6 a). Our previous result indicated that Fe precipitates and the Cu matrix had a cube-on-cube orientation relationship [ 21 ]. Magnetization curves of both the Fe-free alloy and the Fe-doping alloy after a heat treatment, aged at 550 °C for 4 h, are shown in Figure 6 b.…”
Section: Resultsmentioning
confidence: 99%
“…This Cu–Fe alloy also serves as a good candidate for conductive materials, because of the low costs of iron compared to other insoluble elements [ 6 , 20 , 21 ], as well as its excellent mechanical properties [ 22 , 23 ]. According to the Cu–Fe phase diagram [ 24 ], the maximum solubility of iron in copper is 4.1 wt %, and its minimum solid solubility at room temperature is significantly lower than 1 wt %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase in the strength is generally accompanied by a decrease in the electrical conductivity, and vice versa [38][39][40][41][42]. Our group applied SMFs to control the microstructures during the solidification process of the alloys in order to improve the tradeoffs between strength and electrical conductivity [43][44][45][46]. Figure 2 shows the comparison of Cu-Fe alloys by using SMFs in different processes.…”
Section: High Strength High Conductivity Cu-based Alloys Treated By Smfsmentioning
confidence: 99%
“…Sometimes they can also be used as bacteriostatic biomaterials [1][2][3][4][5][6][7][8]. Microalloying is usually used by material researchers to maintain the alloy's high electric conductivity and mechanical properties [9,10]. The high strength of alloys is due to nanoscale precipitates in the copper matrix during the aging process.…”
Section: Introductionmentioning
confidence: 99%